2020
DOI: 10.1002/cpt.1864
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine Dosing Recommendations for Pediatric COVID‐19 Supported by Modeling and Simulation

Abstract: As chloroquine (CHQ) is part of the Dutch Centre for Infectious Disease Control coronavirus disease 2019 experimental treatment guideline, pediatric dosing guidelines are needed. Recent pediatric data suggest that existing World Health Organization (WHO) dosing guidelines for children with malaria are suboptimal. The aim of our study was to establish best-evidence to inform pediatric CHQ doses for children infected with COVID-19. A previously developed physiologically-based pharmacokinetic (PBPK) model for CH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…The current situation surrounding COVID-19 requires fast decision in clinical trial design with limited information, consequently, resulting in a potentially higher risk or lower benefit. A few such examples include higher incidence of side effects for chloroquine and lack of benefit from lopinavir and ritonavir combination therapy [32,33]. COVID patients who received chloroquine with azithromycin experienced QTc prolongation, which may be attributed to PK or PD changes in target tissues as a result of DDI.…”
Section: Discussionmentioning
confidence: 99%
“…The current situation surrounding COVID-19 requires fast decision in clinical trial design with limited information, consequently, resulting in a potentially higher risk or lower benefit. A few such examples include higher incidence of side effects for chloroquine and lack of benefit from lopinavir and ritonavir combination therapy [32,33]. COVID patients who received chloroquine with azithromycin experienced QTc prolongation, which may be attributed to PK or PD changes in target tissues as a result of DDI.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical pharmacologists have a wealth of knowledge about approved drugs, many of which are currently in clinical trials for repurposing. This knowledge can be harnessed and translated immediately to optimize dosing and treatment regimens: Absorption, distribution, metabolism, and pharmacokinetics; Pharmacokinetics in special populations and the role of factors such as age (including pediatrics 5 and geriatrics), gender, ethnicity, morphometry, disease, and organ function; Drug–drug interactions (DDIs): infectious diseases are often best treated with more than one drug, and several potential combination therapies have already been proposed for COVID‐19 2 . In addition, age is associated with concomitant medications, which may cause DDIs with COVID‐19 drugs, especially those commonly used in older people; Pharmacogenomics and precision medicine; Relationship between pharmacokinetics and pharmacodynamics (biomarker) response; Relationship between exposure and adverse events 6,7 …”
Section: Figurementioning
confidence: 99%
“…As a traditional antimalaria agent, WHO has released guidelines for the treatment of malaria; however, there was little content concerning the efficacy and safety of CQ treatment in pediatrics. Laurens et al reported CQ dosing recommendation for pediatrics based on PBPK modeling: 35 mg/kg (CHQ base) for children 0 to 1 month, 47 mg/kg for 1-6 months, 55 mg/kg for 6 months-12 years, and 44 mg/kg for adolescents and adults, not to exceed 3,300 mg in any patient (Verscheijden et al, 2020). With cautions that the lethal toxicity in children has been reported as unintentional overdoses of~35-100 mg/kg of CQ (base) in a single dose (Verscheijden et al, 2020).…”
Section: Pediatricsmentioning
confidence: 99%
“…Laurens et al reported CQ dosing recommendation for pediatrics based on PBPK modeling: 35 mg/kg (CHQ base) for children 0 to 1 month, 47 mg/kg for 1-6 months, 55 mg/kg for 6 months-12 years, and 44 mg/kg for adolescents and adults, not to exceed 3,300 mg in any patient (Verscheijden et al, 2020). With cautions that the lethal toxicity in children has been reported as unintentional overdoses of~35-100 mg/kg of CQ (base) in a single dose (Verscheijden et al, 2020). Currently, diagnosis and treatment recommendation for pediatric COVID-19 released by China National Clinical Research Center for Child Health was not recommended CQ in pediatrics.…”
Section: Pediatricsmentioning
confidence: 99%